Socioeconomic status hypothesis in asthma and eczema in young adolescents - Vlaski E; Stavric, Katerina; Isjanovska, Rozalinda; Seckova, Lidija; Kimovska, Milica (The Balkan Societies of Allergology and Clinical Immunology, 2006)
Background: As studies in different populations have shown conflicting results about the relationship between asthma and socioeconomic status and its association with eczema has been less extensively studied, the study was aimed to explore the socioeconomic status hypothesis in asthma and eczema in young adolescents in the Republic of Macedonia. Methods: The self-reported data from 3026 children aged 13/14 years from randomly selected schools in Skopje, the capital of Macedonia, were obtained through the standardized International Study of Asthma and Allergies in Childhood Phase Three written questionnaires. Family size, mother’s educational level, tobacco smoke at home, wood/coal/oil heating at home and body mass index, as some socioeconomic status measures, were statistically correlated to asthma and eczema symptoms by odds ratios with 95% confidence interval (OR, 95% CI) in binary logistic regression. Results: Small families and overweight significantly increased the risk of ever-diagnosed asthma (OR 2.160, 95% CI 1.110-4.203 P=0.023 and OR 2.085, 95% CI 1.109-3.922 P=0.023, respectively). As well overweight was significantly associated with increased risk of current night cough (OR 1.365, 95% CI 1.053-1.771 P=0.019), while mother’s university education with decreased risk of the same symptom (OR 0.759, 95% CI 0.620-0.930 P=0.008). A significant association between the severity of asthma, eczema and investigated measures of socioeconomic status was not found. Conclusion: The results support the positive association between socioeconomic status and asthma only, without any effect of socioeconomic status on asthma severity and eczema.
Keywords: adolescents; asthma; eczema; socioeconomic factors